Early asthma control and maintenance with eformoterol following reduction of inhaled corticosteroid dose. Issue 9 (1st September 2002) - Price, D; Dutchman, D; Mawson, A; Bodalia, B; Duggan, S; Todd, P
Abstract : Background: Previous studies have indicated the benefits of adding long acting β2 agonists to inhaled corticosteroids in the maintenance treatment of moderate to severe asthma. The effects of adding eformoterol to corticosteroids on asthma control and exacerbations in patients with mild to moderate asthma were studied. Methods: After a run in period of 7–14 days on existing medication, 663 symptomatic patients were randomised to receive budesonide Turbohaler 400 μg twice daily together with either eformoterol Turbohaler 9 μg (delivered dose) or placebo twice daily. After 4 weeks patients whose asthma was well controlled (n=505) were re-randomised to receive budesonide 400 μg daily and either eformoterol 9 μg or placebo twice daily for a further 6 months. Results: Patients receiving eformoterol achieved asthma control 10 days sooner than those receiving budesonide alone, and improvements in lung function, symptoms, quality of life, and relief β2 agonist use were significantly greater with eformoterol. During the 6 month follow up the frequency of mild exacerbations was significantly lower in the eformoterol group than in those receiving budesonide alone (7.2 versus 10.5 per patient, 95% confidence interval for ratio 0.49 to 0.96, p=0.03). The time to first day of poorly controlled asthma was 97 days in the eformoterol group compared with 42 days in the placebo group (p=0.003). Conclusions: Adding eformoterol to a low or moderate dose of budesonide in mild asthma resulted in faster and more effective control than treatment with budesonide alone. Eformoterol allowed the corticosteroid dose to be reduced while also decreasing the rate of mild exacerbations compared with budesonide alone. These data suggest a therapeutic advantage of adding eformoterol to inhaled corticosteroids in patients with mild to moderate asthma.